Resentment's virtue: Jean Améry and the refusal to forgive - Brudholm, Thomas (Politics, history, and social change)
Dwelling on the negative -- Alchemies of reconciliation after mass atrocity -- Anger, resentment, and ressentiment -- Philosophy on the border -- Book outline -- Revisisiting the truth and reconciliation commission of South Africa -- Commissioning anger -- Re-viewing a miracle -- The truth and reconciliation commission of South Africa -- The hearings -- This is not a court of law -- Forgiving and its alternatives -- Facing resistance -- The therapy of anger -- What victims feel and want -- Getting on with life -- The lures of the therapeutic perspective -- Desmond tutu on anger -- Those who will not forgive resentment : a legitimate moral sentiment? -- Anger, Ubuntu, and social harmony -- Boosterism of forgiveness -- Layers and remainders -- Nested resentments -- Acknowledging remainders : the constitutional court -- Tansition to part two -- Jean Améry on resentment and reconciliation -- Contextualizing "ressentiments" -- From South Africa to post-war Germany -- Jean Améry : life and works -- Beyond guilt and atonement -- Germany, 1945-1965 -- Reading "ressentiments" -- Opening moves -- From clarification to justification -- Reimagining ressentiment -- The origins of Améry's ressentiment -- Reforming ressentiment -- Facing the irreversible -- The zustand passage -- The twisted sense of time -- The absurd demand -- Changing the past or its significance--to the present? -- Ambiguities of ressentiment and reconciliation -- Restoring coexistence -- Moral conflict resolution -- Ressentiment and the release from abandonment -- Rehabilitating the "man of ressentiment" -- Guilt and responsibility -- Collective guilt -- Heirs to responsibility -- Wishful thinking? -- A moral daydream -- Resentment and self-preoccupation -- Awakening -- A multifarious reception -- Heyd and Chaumont -- Neiman and Amben -- Walker and Remtma